1902 R.I. Pub. Laws 67 - (:unkn) unknown (My University, 1902)
An Act in addition to chapter 40 of the General Laws, Entitled “Of the Town Council,” § 1: Town councils and city councils may from time to time make and ordain all ordinances and regulations for their respective towns, not repugnant to law, which they may deem necessary for the safety of their inhabitants from the manufacture, storage, keeping, having in possession, transportation, sale, or use of gunpowder, gun-cotton, dynamite, nitro-glycerine, nitro-gelatine, lyddite, chlorate of potash, picric acid, sodium calcium carbide, acetylene gas, gasoline gas, and any and all other explosives and explosive chemicals; and may prohibit the manufacture, storage, keeping having in possession, transportation , sale , or use by any and all persons or persons of any or all said substances and gases in their respective towns, unless a license for the same shall be first obtained from the town council or board of aldermen, which license shall be for the term of one years from the date thereof unless sooner revoked by order of said town council or board of aldermen.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER